2020
DOI: 10.1021/acs.jmedchem.0c01277
|View full text |Cite
|
Sign up to set email alerts
|

Cancer Cell Resistance Against the Clinically Investigated Thiosemicarbazone COTI-2 Is Based on Formation of Intracellular Copper Complex Glutathione Adducts and ABCC1-Mediated Efflux

Abstract: COTI-2 is a novel anticancer thiosemicarbazone in phase I clinical trial. However, the effects of metal complexation (a main characteristic of thiosemicarbazones) and acquired resistance mechanisms are widely unknown. Therefore, in this study, the copper and iron complexes of COTI-2 were synthesized and evaluated for their anticancer activity and impact on drug resistance in comparison to metal-free thiosemicarbazones. Investigations using Triapine-resistant SW480/Tria and newly established COTI-2-resistant SW… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
33
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(33 citation statements)
references
References 43 publications
0
33
0
Order By: Relevance
“…In contrast to NSC319726, COTI-2 did not affect intracellular Zn accumulation in HNSCC-mutant TP 53 cells, indicating that its mechanism of action might be independent of Zn chelation [ 267 ]. The activity of COTI-2 was significantly potentiated by coordination to a Cu(II) center and decreased upon coordination to a Fe(II) center, suggesting that Cu plays an important role in the mechanism of action of COTI-2 [ 271 ]. Recently it was revealed that resistant profile of both COTI-2 and its Cu(II) complex was governed by GSH-dependent ABCC1 efflux pump [ 271 ].…”
Section: Modulating Intratumoral Cu Levels With Metal-binding Ligandsmentioning
confidence: 99%
See 2 more Smart Citations
“…In contrast to NSC319726, COTI-2 did not affect intracellular Zn accumulation in HNSCC-mutant TP 53 cells, indicating that its mechanism of action might be independent of Zn chelation [ 267 ]. The activity of COTI-2 was significantly potentiated by coordination to a Cu(II) center and decreased upon coordination to a Fe(II) center, suggesting that Cu plays an important role in the mechanism of action of COTI-2 [ 271 ]. Recently it was revealed that resistant profile of both COTI-2 and its Cu(II) complex was governed by GSH-dependent ABCC1 efflux pump [ 271 ].…”
Section: Modulating Intratumoral Cu Levels With Metal-binding Ligandsmentioning
confidence: 99%
“…The activity of COTI-2 was significantly potentiated by coordination to a Cu(II) center and decreased upon coordination to a Fe(II) center, suggesting that Cu plays an important role in the mechanism of action of COTI-2 [ 271 ]. Recently it was revealed that resistant profile of both COTI-2 and its Cu(II) complex was governed by GSH-dependent ABCC1 efflux pump [ 271 ]. It was shown that COTI-2/Cu complex formed stable and non-reducible adduct with GSH, which was recognized by ABCC1 and pumped out of the COTI-2-resistant cancer cells [ 271 ].…”
Section: Modulating Intratumoral Cu Levels With Metal-binding Ligandsmentioning
confidence: 99%
See 1 more Smart Citation
“…As can be observed in Table 3, the semicarbazone derivatives (22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32) were much less active, having significant FAR values only at 2 µM. As with azine derivatives, compounds sharing aromatic substituents (25-32) showed higher activity (FAR values = 3.20-8.77) than those with aliphatic moieties (22)(23)(24).…”
Section: Inhibition Of P-glycoprotein Efflux Activitymentioning
confidence: 93%
“…The monoterpene indole alkaloid of the corynanthe-type [18], dregamine (1), was previously isolated, in a large amount, from the alkaloid fraction of the methanol extract of Tabernaemontana elegans roots [13]. As mentioned above, dregamine (1) derivatives were reported as promising MDR reversers [13][14][15], prompting us to carry out new chemical modifications to obtain 19 azines (3-21) and 11 semicarbazone (22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32) derivatives.…”
Section: Chemistrymentioning
confidence: 99%